NOTES ON NEW GUINEA PLANTS-IV* Saccopetalum koolsii Kostermans, sp. nov. (Annonaceae) - KOSTERMANS, A. J. G. H. (Research Center for Biology, 1952)
During the exploration of the Momi-Ransiki region, about 80 km south of Manokwari on the west coast of the Geelvink Bay in Netherlands New Guinea in 1948,our party collected several specimens of a rather common,although scattered Annonaceous tree,which was locally called mies (pronounce: meece).I was lucky to find one tree in flower in the neighbourhood of the Warnapi (war = river), north of Ransiki.After examination the species appeared to belong to the genus Saccopetalum Benn.,hitherto unknown from New Guinea.In honour of Dr. J.Kools,at that time in charge of the Division of Planning (nowadays Professor at the State Agricultural University of Wageningen, The Netherlands), who took a lively interest in the exploration of this area, this species is called